Erotic subjects : the sexuality of politics in early modern English literature - Sanchez, Melissa E. (New York ; Oxford : Oxford University Press, 2011)
This volume demonstrates that if we treat 16th- and 17th-century erotic literature as part of English political history, both fields of study will look rather different. Sanchez traces implications of two early modern commonplaces.
Includes bibliographical references and index.
Description based on print version record.
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; Politics and literature; Sex (Psychology); Literature and society -- England -- History -- 16th century; Literature and society -- England -- History -- 17th century